Solving Systems using Substitution 5.2 Solving Systems using Substitution
Evaluate if x = 2 and y = -3 3x + y 5x + 3(x+y) – 2y
Solve for x: 3) 3(x-2) = 6 4) 7 – 3(2 + 5x) = 11
5) Solve the system of equations using substitution: y = 3x x + 2y = -21
6) Solve the system of equations using substitution: x+y = -3 y = 2x +6
7) Solve the system of equations using substitution: -4x + 2y = 6 y = 2x + 3
8) Solve the system of equations: x + 5y = -3 3x – 2y = 8
9) Solve the system of equations: 2x + y = -4 5x + 3y = -6
10) Solve the system of equations: a + b = 1 5a + 3b = -1
11) Solve the system of equations: y = 4x + 2 y= 2x - 8
Unit 5 Assignment #3 p. 263 #8-19all, 32*, 35-37 *EXTRA CREDIT